(untitled) (Journal of Partial Differential Equations, 1997)
In this paper, we obtain that the number of determining nodes for the generalized Ginzburg-Landau equation is two closely points, as a consequence, an upper bound for the winding number of stationary is established in terrns of the parameters in the equation. It is also proven that the fractal dimension of the set of stationary solution is less than or equal to 4.